CFD study of heat transfer and fluid flow in a parabolic trough solar receiver with internal annular porous structure and synthetic oil–Al2O3 nanofluid. (January 2020) - Bozorg, Mehdi Vahabzadeh; Hossein Doranehgard, Mohammad; Hong, Kun; Xiong, Qingang
Abstract: In this study, a finite volume method is employed to investigate the performance of a novel parabolic trough solar collector with synthetic oil–Al2 O3 nanofluid as the heat transfer fluid. An annular porous structure is installed inside the absorber tube to improve heat transfer. The effects of the simultaneous utilization of porous structure and nanoparticle addition on heat transfer, pressure drop, and thermal efficiency of the receiver are investigated for different values of Reynolds number, volume fraction of nanoparticle, inlet temperature and Darcy number of the porous region. The results show that as Reynolds number and volume fraction of nanoparticle increase, heat transfer coefficient, pressure drop, and thermal efficiency increase. However, the increases in inlet temperature lead to the decreases in heat transfer coefficient, pressure drop, and thermal efficiency. At Reynolds numbers higher than 30 × 10 4, simultaneous utilization of porous structure with Da = 0.3 and nanoparticles increases heat transfer coefficients nearly 7% and 20%, pressure drops up to 42.5% and 42%, thermal efficiencies up to 8% and 15%, overall efficiencies nearly 5% and 14%, and exergetic efficiencies by 7% and 15% for inlet temperature of 500 and 600 K, respectively. Highlights: Simultaneous utilization of porous structure and nanofluid are investigated. Nanoparticle addition and porous structure are recommended at high HTF flow rates. HTF with lower inlet temperatures provides higher thermal efficiencies. Installing inner porous annular structure increases thermal efficiency up to 13%. Porous structure increases exergetic efficiency of solar collectors by about 15%.